Students’ Level of Understanding on Vocational Higher Education in Depok, West Java - Hikmah, Y (KnE Social Sciences, 2018)
This study discusses the understanding of high school students about Vocational Education. Based on the results of the distribution of questionnaires to students, about 60% of students do not understand about Vocational Education. This is one of the factors of low interest of prospective students to Vocational Program. In fact, Vocational Education is different from Academic Education. Vocational Education emphasizes on the control of work competence so that vocational graduates are workforce-ready to work, to fill both the domestic and international market. By improving community understanding, especially prospective students on Vocational Education, the prospective students can be motivated to continue to vocational education. Therefore, Vocational Education will mostly produce graduates who are ready to work with specific skills that qualify according to the industry’s wishes. Thus, the absorptive power of vocational graduates will be high, resulting in reduced unemployment. Keywords: vocational, unemployment, work